Efecto de la incorporación de harina Amaranthus Dubius sobre la conversión alimenticia del camarón de baja salinidad en etapa post larva - Párraga Vergara, Adriana Lilibeth (2020)
The objective of the research was to value the feed conversion of low salinity shrimp by partially adding 15, 20, 25 and 30% of Amaranthus dubius in the balanced feed. The base mixture was formulated with fish, amaranth, meat, feathers, squid and fish oils, attractants, vitamin C and minerals; which was mixed, pelletized and packed in polyethylene plastic bags. A Completely Random Design (DCA) was applied with four treatments and four replications of each. The physicochemical (protein, ash, acidity, fiber and moisture) and microbiological (salmonella) characterization was carried out, in accordance with the INEN 1767 Standard. The experimental unit consisted of 320 shrimp in post larvae stage distributed in 16 fish tanks, suitable for a constant temperature and aeration system; controlling salinity (4.09 ± 0.01 g / L) and pH (8.05 ± 0.06). For larval development, food was incorporated every 4 hours for 28 days. The growth performance parameters were determined: S (Survival), TCE (Specific Growth Rate), FCA (Food Conversion Factor), EA (Food Efficiency) and TEP (Protein Efficiency Rate). For the physicochemical characterization of the food, the statistically significant difference (<0.05) between the treatments was determined, with T1 being the most suitable. In the evaluation of growth performance, there was no statistical difference (> 0.05) between the treatments; therefore, the incorporation of amaranth in food formulations with fish meal does not influence the growth factors of shrimp in the post larva stage; being advisable to replace up to 30% of animal protein with vegetable protein.